Material flow management of industrial enterprise on lean principles - Kolos, Irina (My University, 2017)
The material flow is characterized as a component of the value stream, where a material form of production stocks changes to a finished product, while creating value for the consumer. The model of the material flow management of an industrial enterprise on the lean basis is proposed with the use of a process approach (on the basis of a set of agreed interrelated purchase/supply processes, production/processing, sales/consumption), a functional approach and a system approach (using specific lean methods within an individual management function) to ensure lean transformations in the material flow. The relevance of the use of a combination of lean production methods in the implementation of individual management functions with the material flow of an industrial enterprise with a focus on continuous improvement of value creation for the consumer.
Keywords: кафедра обліку і аудиту; value stream; flow of material; lean production; industrial production; потік створення цінності; матеріальний потік; ощадливе виробництво; промислове підприємство